B Cell Subset Analysis and Gene Expression Characterization in Mid-Luteal Endometrium - Shen, Mengni; Child, Tim; Mittal, Monica; Sarodey, Geet; Salim, Rehan; Granne, Ingrid; Southcombe, Jennifer H. (Frontiers in Cell and Developmental Biology, 2021)
The human endometrium is the innermost mucosal membrane of the uterus and is the first point of contact for an implanting blastocyst. A wide variety of immune cells are found amongst the endometrial epithelial layers and stromal cells which both provide host immune responses against pathogens and also assist with placentation and pregnancy establishment, however B cells have not been characterized, despite being a vital player in both adaptive and mucosal immunity. Through analysis of mid-luteal endometrial biopsies, we find 1-5% of endometrial immune cells are B cells, the majority were naïve or memory B cells, with few plasma cells. Compared with circulating B cells, endometrial B cells had an activated phenotype, with increased expression of CD69, HLA-DR, CD74 and CD83, and IL-10 production capacities. PD1+CXCR5+ICOS+ T follicular helper-like cells and FAS+IgD−BCL6+ germinal center B cells were also present in the endometrium, which may indicate that endometrial B cells are playing an active role through germinal center reactions in human endometrial environment.